A Systematic Review of Personalized Learning: Comparison between E-Learning and Learning by Coursework Program in Oman - Tawafak, Ragad M.; Awanis, Romli; Malik, Sohail Iqbal; Shakir, Mohanaad; Alfarsi, Ghaliya M. (IJET, 2019)
There is a need for several applications and technologies in higher education institutions in Oman to enhance the educational process. This systematical study investigates the simultaneous influence of technology implementation with e-learning and traditional coursework program instruction on the enhancement and development of an assessment method for undergraduates in different programs. This paper aims to analyze the current articles that handle with the learning process and compare between the understanding and acceptance of E-Learning mechanism and traditional coursework method of teaching for improving assessment method and evaluation of academic performance. The method works on the benefits of increasing E-Learning process for educational skills as an assistance tool with faculty material and class discussion. In this study, surveys were distributed to two different universities and college in Oman to assess their satisfaction in the learning model. The findings of this paper assisted the model that may help to improve both the teaching method and academic performance of student learning outcomes.